Indicadores de desenvolvimento rural : desafios e perspectivas para a sustentabilidade do setor no Município de Laranjal - PR - Loesch, Marcio Giovani (2014)
Family farming is the most Brazilian farmers , who are responsible for producing much of the food that supply Brazil, such as beans , rice, corn, vegetables , cassava, meat and dairy . This paper aims to develop from a relevant diagnostic information about the family farming model adopted in Laranjal - PR, and through indicators evaluating the same, aiming thereby promoting sustainable rural development. As a research tool applied in the form of interviews, we used the questionnaire Ministry of Agrarian Development - MDA, called: Diagnostic Unit Family Production, considering only some data relevant to the study. In this context, we seek to establish some sustainability indicators to evaluate the production system of the study area. Through the construction of an array of descriptors, developed a set of sustainability indicators considering the following dimensions: economic, social and environmental. Data analysis provided information about the family of the county farmers, farms, agricultural techniques and practices used in the properties, besides allowing a close-up view of the forms of marketing the products produced. From certain indicators we can observe some features common to most production units. The diagnosis proves, among other information, the difficulties for mechanization, the risk of soil erosion, lack of organization, limited financial resources, low levels of productivity, and the simple way of life. In general, it is concluded that family agriculture developed in the way that is becomes untenable